PERAN INVESTMENT OPPORTUNITY SET SEBAGAI PEMODERASI PENGARUH KINERJA KEUANGAN, GOODCORPORATE GOVERNANCE DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN - Michael Anderson Sianipar; Susi Dwi Mulyani (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2017)
Firm Values of manufacturing company in Indonesia is influenced by various factors of financial and non-financial that can be measured using financial ratios, good governance, and social responsibility practices in the company. The purpose of this study was to analyze the effect of financial performance proxied by Profitability and Solvability, Good Corporate Governance (GCG), and Corporate Social Responsibility (CSR) on the firm value,with Investment Opportunity set (IOS) as a moderating variable. The firm value in this study was proxied by Tobins’q.The population of this research is manufacturing companywith chemical industry subsectors listed in the Indonesia Stock Exchange (BEI) in 2013-2015. The sampling method used is purposive sampling and acquired 31 companies in this sample. The analytical method used is moderating regression analysis.Based on the results of hypotheses testing, there wasSolvability and IOS had positive effect on firm value, while Profitability, GCG, and CSR had no effect on the firm value. The use of a moderating variable Investment Opportunity Set (IOS) is not able to strengthen the influence of profitability, solvability, GCG and CSR on the firm value.